2019
DOI: 10.1111/aos.14137
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ganglion cell layer cysts in diabetic macular oedema treated with anti‐vascular endothelial growth factor

Abstract: Purpose: To investigate the prevalence and impact of ganglion cell layer cysts (GCLC) in patients with diabetic macular oedema (DME) under continuous anti-vascular endothelial growth factor (VEGF) therapy. Methods: The clinical findings and spectral domain optical coherence devices of baseline visits and follow-up after 12-24 and 36 months of DME patients under continuous anti-VEGF therapy were retrospectively collected and analysed for the impact of GCLC cysts. Previously established prognostic parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Corticosteroids did not show an improved visual acuity compared to VEGF, neither in naive nor in persistent, chronic DME, but on an individual level, some patients may respond better to one, while others respond better to the other treatment approach, which is owed to the multifactorial origin of DME. A post hoc analysis of protocol I have shown that intravitreal steroids have the potential to lead to similar visual acuity improvements as anti-VEGF therapy, at least in pseudophakic eyes, where cataract progression does not impede functional performance [ 18 , 19 , 26 , 54 , 57 , 63 , 64 , 68 , 70 , 76 , 106 , 130 , 135 , 143 , 151 ]. However, they are associated with side effects, such as the development of cataracts and glaucoma, especially in predisposed patients [ 130 , 141 , 144 , 152 ].…”
Section: Discussion and General Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…Corticosteroids did not show an improved visual acuity compared to VEGF, neither in naive nor in persistent, chronic DME, but on an individual level, some patients may respond better to one, while others respond better to the other treatment approach, which is owed to the multifactorial origin of DME. A post hoc analysis of protocol I have shown that intravitreal steroids have the potential to lead to similar visual acuity improvements as anti-VEGF therapy, at least in pseudophakic eyes, where cataract progression does not impede functional performance [ 18 , 19 , 26 , 54 , 57 , 63 , 64 , 68 , 70 , 76 , 106 , 130 , 135 , 143 , 151 ]. However, they are associated with side effects, such as the development of cataracts and glaucoma, especially in predisposed patients [ 130 , 141 , 144 , 152 ].…”
Section: Discussion and General Recommendationmentioning
confidence: 99%
“…An early study proposed that large coalescent macrocysts in severe, long-standing DME may characterize retinal cystoid degeneration and are associated with Müller cell dysfunction and/or necrosis [ 74 ]. The presence of large cystic spaces correlates with greater central subfield thickness, higher prevalence of outer retinal damage, macular ischemia and with diffuse macular edema [ 75 , 76 ]. It is, therefore, not surprising that the sizes of ONL cysts are an important predictive marker for treatment response and functional improvements under anti-VEGF therapy [ 76 ].…”
Section: Morphological Oct Biomarkers In Dmementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, contrary to fluid buildup in the outer nuclear layer (ONL), which is mostly caused by focally leaking microaneurysms, it would appear probable that intraretinal cysts in the inner nuclear layer (INL) caused by widespread artery leakage are more sensitive to anti-VEGF or corticosteroids [ 27 ]. Another crucial factor is the size of the cysts [ 28 ]; in fact, large cysts are characterized as 250-micron horizontally wide foveal cystoid voids [ 27 ] and are associated with increased central subfield thickness, widespread macular edema, macular ischemia, and a higher frequency of outer retinal damage [ 29 ]. Consequently, it should come as no surprise that the ONL cyst diameter is a significant predictor of treatment response and functional gains while receiving anti-VEGF agents [ 29 ].…”
Section: Main Morphological Oct Biomarkers In Dmementioning
confidence: 99%
“…Another crucial factor is the size of the cysts [ 28 ]; in fact, large cysts are characterized as 250-micron horizontally wide foveal cystoid voids [ 27 ] and are associated with increased central subfield thickness, widespread macular edema, macular ischemia, and a higher frequency of outer retinal damage [ 29 ]. Consequently, it should come as no surprise that the ONL cyst diameter is a significant predictor of treatment response and functional gains while receiving anti-VEGF agents [ 29 ]. Several studies demonstrated that switching to a DEX implant improved BCVA in DME with large parafoveal cysts that were resistant to anti-VEGF therapy [ 30 , 31 ].…”
Section: Main Morphological Oct Biomarkers In Dmementioning
confidence: 99%